POSS (Polyhedral Oligomeric Silsesquioxane)-containing single-ion conductor interpenetrating network polymer electrolyte membrane and preparation method thereof

By introducing POSS structure and interpenetrating network design into single-ion conductor electrolytes, the problem of low ion conductivity in room temperature of traditional single-ion polymer electrolytes is solved, high lithium ion mobility and conductivity are achieved, and the performance of lithium metal batteries is improved.

CN119899140AActive Publication Date: 2025-04-29SHANGHAI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510086508.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

Traditional single-ion polymer electrolytes have low room temperature ionic conductivity, making it difficult to meet the needs of high-energy density lithium metal batteries.

Method used

Using a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS, a sulfonimide lithium salt monomer containing a methacrylamide structure is prepared, and a free radical polymerization is initiated with a polymerizable POSS structure, EO segment and crosslinking agent through two steps to form an interpenetrating network structure.

Benefits of technology

The number of lithium ion migration and room temperature ion conductivity are significantly improved, the electrochemical window is expanded, the electrode-electrolyte compatibility is enhanced, and the cycling performance of lithium metal batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899140A_ABST
    Figure CN119899140A_ABST
Patent Text Reader

Abstract

The invention discloses a POSS (Polyhedral Oligomeric Silsesquioxane)-containing single ion conductor interpenetrating network polymer electrolyte membrane and a preparation method thereof, and relates to the field of polymer electrolytes.The preparation method comprises the steps that firstly, a sulfonimide lithium salt monomer containing a methacrylamide structure is prepared, and the sulfonimide lithium salt monomer is mixed with a polymerizable POSS structure, an EO chain segment and a cross-linking agent to prepare a polymer electrolyte membrane; the POSS-containing single-ion conductor interpenetrating network polymer electrolyte membrane is constructed through two-step photo-initiated free radical polymerization. The problem that the ionic conductivity of a single-ion electrolyte is obviously lower than that of a traditional double-ion electrolyte is solved, the ionic conductivity and the lithium ion transference number are effectively improved, and the prepared electrolyte membrane has a wide electrochemical window and good electrode-electrolyte compatibility; and the lithium metal battery assembled by the composite material has good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer electrolytes, and in particular to a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS and a preparation method thereof. Background Art

[0002] In the context of global energy structure adjustment to cope with environmental and energy crises, achieving efficient and safe energy storage is an important driving force for the development of modern human society. -1 ) and lower electrode potential (-3.04V relative to the standard hydrogen electrode), making lithium metal batteries promising to become the next generation of high energy density energy storage devices. However, traditional liquid electrolytes can cause severe polarization on the electrode surface, leading to uneven deposition of lithium ions and the formation of needle-shaped lithium dendrites, which can then pierce the diaphragm to cause electrolyte leakage and battery short circuit, causing safety issues. Therefore, the development of solid electrolytes with good safety, chemical stability and mechanical strength is the key to the development of the next generation of high energy density lithium metal batteries.

[0003] Traditional dual-ion polymer electrolytes contain free lithium salts. Since lithium ions are more easily combined with Lewis bases, the mobility of lithium ions is much lower than that of anions. Therefore, the lithium ion migration number is usually lower than 0.3, which causes the generation of anion concentration gradients, leading to polarization, side reactions, increased internal resistance, and other situations that endanger battery safety. For single-ion polymer electrolytes, since anions are fixed or bound, the ions actually used for conduction are mainly lithium ions. Due to the high lithium ion migration number, single-ion polymer electrolytes can almost avoid the generation of concentration gradients and inhibit the growth of lithium dendrites.

[0004] Since the ions used for conduction in the electrolyte are almost all lithium ions, the ionic conductivity of single-ion electrolytes is significantly lower than that of traditional double-ion electrolytes. How to improve the room temperature ionic conductivity of single-ion polymer electrolytes is the most urgent problem currently faced. Summary of the invention

[0005] In view of this, an object of the present invention is to provide a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS and a preparation method thereof.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] <First aspect>

[0008] The present invention provides a single ion conductor monomer, which is a sulfonimide lithium salt monomer containing a methacrylamide structure, and the single ion conductor monomer has a structural formula of:

[0009]

[0010] <Second Aspect>

[0011] The present invention provides a method for preparing the above-mentioned single ion conductor monomer, comprising the following steps:

[0012] The intermediate II and lithium hydroxide are dissolved in a third solvent, methacryloyl chloride is added under low temperature, and then after sufficient reaction at 20-30° C., the product is extracted to obtain the single ion conductor monomer. The intermediate II has the structural formula: The low temperature environment is -5 to 5°C.

[0013] As an embodiment, the molar ratio of the intermediate II, methacryloyl chloride and lithium hydroxide is 1:(1-1.2):(1-1.2).

[0014] As an embodiment, the third solvent is one or more of acetone and acetonitrile.

[0015] As an embodiment, the preparation method of the intermediate II is: dissolving the intermediate I, ferric chloride and palladium carbon catalyst in a second solvent, adding hydrazine hydrate at 65-75° C., and continuing to reflux at 65-75° C. After the reaction is completed, extracting the product to obtain the intermediate II, the structural formula of the intermediate I is:

[0016]

[0017] As an embodiment, the mass ratio of the intermediate I, ferric chloride and palladium-carbon catalyst is 100:(3-10):(5-15).

[0018] In some embodiments, the mass ratio of the intermediate I, ferric chloride and palladium-carbon catalyst is 100:5:5.

[0019] As an embodiment, the mass ratio of the intermediate I and hydrazine hydrate is 1:(1.2-1.5).

[0020] As an embodiment, the mass ratio of the intermediate I and hydrazine hydrate is 2:3.

[0021] As an embodiment, the second solvent is one or more of anhydrous ethanol and anhydrous methanol.

[0022] As an embodiment, the preparation method of the intermediate I is: dissolving trifluoromethanesulfonamide, p-nitrobenzenesulfonyl chloride and a strong base in a first solvent, reacting them sufficiently under a low temperature environment, and extracting the product to obtain the intermediate I.

[0023] As an embodiment, the molar ratio of trifluoromethanesulfonamide, p-nitrobenzenesulfonyl chloride and the strong base is 1:(1-1.2):(2-2.2).

[0024] As an embodiment, the strong base is one or more of potassium hydroxide, sodium hydroxide, and lithium hydroxide.

[0025] As an embodiment, the first solvent is one or more of acetone and acetonitrile.

[0026] In some embodiments, the strong base is potassium hydroxide, the first solvent is acetone, the second solvent is anhydrous ethanol, and the third solvent is acetone.

[0027] As an embodiment, in step S12, hydrazine hydrate is added to the reaction system by slow dropwise addition.

[0028] As an embodiment, in step S13, methacryloyl chloride is added to the reaction system by slow dropwise addition.

[0029] As an embodiment, the slow dripping is: controlling the dripping rate to 3 to 5 seconds per drop by a constant pressure dropping funnel.

[0030] <Third Aspect>

[0031] The present invention provides the use of the single ion conductor monomer.

[0032] The single ion conductor monomer is used for preparing an electrolyte membrane of a lithium ion battery.

[0033] <Fourth Aspect>

[0034] The present invention provides a method for preparing a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS, comprising the following steps:

[0035] S21, configure a precursor solution I containing poly (vinylidene fluoride - hexafluoropropylene), configure a precursor solution II containing a POSS material and a cross-linking agent;

[0036] S22, after mixing the precursor solution I and the precursor solution II, adding the first portion of the initiator, stirring at 65-75° C. to form a uniform solution, and then irradiating with ultraviolet light for the first time to initiate free radical polymerization;

[0037] S23, adding polyethylene glycol diacrylate, single ion conductor monomer and the second initiator to the solution treated in step S22, stirring at 65-75° C. to obtain a uniform slurry;

[0038] S24, coating the slurry on a substrate to obtain a wet film, and subjecting the wet film to a second ultraviolet irradiation to initiate free radical polymerization, and then drying to obtain an initial film;

[0039] S25, soaking the initial membrane in an electrolyte to obtain a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS;

[0040] Wherein, the single ion conductor monomer structural formula is:

[0041]

[0042] As an embodiment, the POSS material is methacrylate type polyhedral oligomeric silsesquioxane.

[0043] As an embodiment, the POSS material is one or more of heptaisobutylmethacryloxypropyl oligomeric silsesquioxane, heptaisooctylmethacryloxypropyl oligomeric silsesquioxane, heptaphenylvinyl oligomeric silsesquioxane, and heptaphenylallyl oligomeric silsesquioxane.

[0044] In some embodiments, the POSS material is hepta-isooctylmethacryloxypropyl oligomeric silsesquioxane.

[0045] As an embodiment, the crosslinking agent is one or more of pentaerythritol tetraacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate, and pentaerythritol tetra-3-mercaptopropionate.

[0046] In some embodiments, the crosslinking agent is pentaerythritol tetraacrylate.

[0047] As an embodiment, the first initiator is one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzoin diethyl ether, and benzoin dimethyl ether.

[0048] As an embodiment, the second initiator is one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzoin diethyl ether, and benzoin dimethyl ether.

[0049] In some embodiments, the first initiator and the second initiator are both 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0050] As an embodiment, the mass ratio of poly(vinylidene fluoride-hexafluoropropylene), POSS material, crosslinking agent, first initiator, polyethylene glycol diacrylate, single ion conductor monomer and second initiator is: 10:(2.5-10):1.5:0.5:35:30:0.7.

[0051] In some embodiments, the mass ratio of poly(vinylidene fluoride-hexafluoropropylene), POSS material, crosslinker, first initiator, polyethylene glycol diacrylate, single ion conductor monomer and second initiator is: 10:5:1.5:0.5:35:30:0.7.

[0052] As an embodiment, the solvent in the precursor solution I is one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, acetone, and isopropanol.

[0053] In some embodiments, the solvent in the precursor solution I is N,N-dimethylformamide.

[0054] As an embodiment, the solvent in the precursor solution II is one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, acetone, and isopropanol.

[0055] In some embodiments, the solvent in the precursor solution II is isopropanol.

[0056] As an embodiment, the ultraviolet irradiation is irradiation under 365nm ultraviolet light for 10 to 15 minutes.

[0057] In some embodiments, the first ultraviolet irradiation is irradiation with 365 nm ultraviolet light for 10 min.

[0058] In some embodiments, the second ultraviolet irradiation is irradiation with 365 nm ultraviolet light for 10 min.

[0059] As an embodiment, in step S24, the drying temperature is 65-75°C.

[0060] As an embodiment, in step S25, the electrolyte is EC / V DEC =1 / 1 configured electrolyte.

[0061] As an embodiment, in step S25, the soaking treatment time is 20 to 30 minutes.

[0062] In some embodiments, in step S25, the soaking treatment time is 20 minutes.

[0063] <Fifth Aspect>

[0064] The invention provides a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS, which is prepared by the preparation method of the single ion conductor interpenetrating network polymer electrolyte membrane containing POSS.

[0065] As an embodiment, the single ion conductor interpenetrating network polymer electrolyte membrane containing POSS has a lithium ion transference number of 0.78 to 0.85 and a -5 S cm -1 Room temperature ionic conductivity.

[0066] As an embodiment, the single ion conductor interpenetrating network polymer electrolyte membrane containing POSS has a lithium ion transference number of 0.84 to 0.85 and a -5 S cm -1 Room temperature ionic conductivity.

[0067] In some embodiments, the single ion conductor interpenetrating network polymer electrolyte membrane containing POSS has a lithium ion transference number of 0.85 and a -5 S cm -1 Room temperature ionic conductivity.

[0068] Compared with the prior art, the present invention has the following beneficial effects:

[0069] 1) The present invention first provides a method for preparing a single-ion conductor monomer, prepares a sulfonyl imide lithium salt monomer containing a methacrylamide structure, and applies the prepared single-ion conductor monomer to the preparation of a single-ion conductor interpenetrating network polymer electrolyte membrane containing POSS, and combines it with a polymerizable POSS structure, an EO segment and a cross-linking agent to obtain an interpenetrating network structure through two-step photoinitiated free radical polymerization, which can effectively improve the ionic conductivity and the lithium ion migration number, and the electrolyte has a wide electrochemical window of 5.2V and good electrode-electrolyte compatibility, and the lithium metal battery assembled from the monomer has good cycle performance and can cycle 600 times at a current density of 1C.

[0070] 2) The electrolyte membrane provided by the present invention has the advantages of high safety, simple synthesis method, low production cost, large-scale production, etc., and also has a high lithium ion migration number and ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0072] Figure 1 The hydrogen nuclear magnetic resonance spectrum of the intermediate I prepared in Example 1 of the present invention;

[0073] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of the intermediate II prepared in Example 1 of the present invention;

[0074] Figure 3This is a hydrogen nuclear magnetic resonance spectrum of the single ion conductor monomer LiMATFSI prepared in Example 1 of the present invention;

[0075] Figure 4 This is the AC impedance spectrum of the electrolyte membrane prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0076] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0077] For ease of understanding, the abbreviations or nouns mentioned below are first explained:

[0078] POSS: polyhedral oligomeric silsesquioxane;

[0079] MAPOSS: methacrylate type polyhedral oligomeric silsesquioxane. In this embodiment, hepta-isooctyl methacryloyloxypropyl oligomeric silsesquioxane is selected. The monomer structure is:

[0080]

[0081] LiMATFSI: lithium (4-methacrylamidobenzenesulfonyl)(trifluoromethylsulfonyl)imide;

[0082] LiTFSI: lithium bis(trifluoromethanesulfonyl)imide;

[0083] PVDF-HFP: poly(vinylidene fluoride-hexafluoropropylene), average molecular weight 400,000;

[0084] PEGDA: polyethylene glycol diacrylate, average molecular weight 1000;

[0085] PETEA: pentaerythritol tetraacrylate;

[0086] HMPP: 2-hydroxy-2-methyl-1-phenyl-1-propanone;

[0087] DMF: N,N-dimethylformamide.

[0088] First, a method for preparing a single ion conductor monomer is introduced through Examples 1 to 3.

[0089] Example 1

[0090] A method for preparing a single ion conductor monomer (LiMATFSI), the specific steps are as follows:

[0091] S11. Dissolve 14.9 g (0.1 mol) of trifluoromethanesulfonamide, 22.1 g (0.1 mol) of 4-nitrobenzenesulfonyl chloride (also known as p-nitrobenzenesulfonyl chloride) and 11.2 g (0.2 mol) of potassium hydroxide in acetone and react at 0°C. After the reaction is completed, filter, rotary evaporate, wash and dry the reaction solution to obtain a white solid powder, which is intermediate I. The hydrogen nuclear magnetic resonance spectrum is as follows: Figure 1 As shown; the structural formula is as follows:

[0092]

[0093] S12, 37.2g (0.1mol) of intermediate I, ferric chloride and palladium carbon catalyst were dissolved in anhydrous ethanol, hydrazine hydrate was slowly added dropwise at 70°C, and reflux reaction was continued at 70°C after the addition was completed. After the reaction was completed, the reaction solution was filtered, rotary evaporated, washed and dried to obtain a yellowish brown solid powder, which was intermediate II. The hydrogen nuclear magnetic resonance spectrum was as follows: Figure 2 As shown; the structural formula is as follows:

[0094]

[0095] S13. Dissolve 34.2 g (0.1 mol) of intermediate II and 2.4 g (0.1 mol) of lithium hydroxide in acetone, slowly drop 10.4 g (0.1 mol) of methacryloyl chloride at 0°C, and react at room temperature after the addition is completed. After the reaction is completed, filter, rotary evaporate, wash, and dry the reaction solution to obtain a light yellow solid powder, which is a single ion conductor monomer (LiMATFSI).

[0096] It should be noted that:

[0097] In steps S11, S12, and S13, the washing and drying treatments are specifically as follows: washing the product three times with dichloromethane, and then drying at 70°C;

[0098] In step S11, an ice bath was used at 0°C and the reaction time was 24 h to ensure sufficient reaction;

[0099] In step S12, the amount of ferric chloride and palladium carbon catalyst is 5wt.% of the amount of intermediate I, and the amount of hydrazine hydrate is 150wt.% of the amount of intermediate I;

[0100] In step S12, hydrazine hydrate is slowly added dropwise, and the dropping rate is controlled to be 3 to 5 seconds per drop by a constant pressure dropping funnel;

[0101] In step S13, methacryloyl chloride is slowly added dropwise, and the dropping rate is controlled to be 3 to 5 seconds per drop by a constant pressure dropping funnel;

[0102] In step S12, the reflux reaction time is 5 h to ensure sufficient reaction;

[0103] In step S13, an ice bath was used at 0°C and the reaction time was 24 h to ensure sufficient reaction.

[0104] In this embodiment, the acetone or anhydrous ethanol involved is used as a solvent, and its amount should in principle be enough to dissolve all the reactants. In this example, the amount of acetone used in steps S11 and S13 is 100 ml, and the amount of anhydrous ethanol used in step S12 is 500 ml.

[0105] The H NMR spectrum of LiMATFSI is as follows Figure 3 As shown, the molecular structure of LiMATFSI is determined as follows:

[0106]

[0107] Example 2

[0108] A method for preparing a single ion conductor monomer (LiMATFSI), the steps are basically the same as those in the above embodiment 1, except that:

[0109] In step S11, the molar ratio of trifluoromethanesulfonamide, 4-nitrobenzenesulfonyl chloride and potassium hydroxide is 1:1.2:2.

[0110] Example 3

[0111] A method for preparing a single ion conductor monomer (LiMATFSI), the steps are basically the same as those in the above embodiment 1, except that:

[0112] In step S13, the molar ratio of the intermediate II, methacryloyl chloride and lithium hydroxide is 1:1.2:1.2.

[0113] Next, the preparation method of the single ion conductor interpenetrating network polymer electrolyte membrane containing POSS is introduced through Examples 4 to 6.

[0114] Example 4

[0115] A method for preparing a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS, the specific steps are as follows:

[0116] S21, adding PVDF-HFP to solvent A to dissolve, configuring to precursor solution I, adding POSS material and cross-linking agent to solvent B to dissolve, configuring to precursor solution II;

[0117] S22, after mixing precursor solution I and precursor solution II, adding the first portion of initiator, stirring at 70° C. to form a uniform solution, and irradiating with 365 nm ultraviolet light for 10 min to initiate free radical polymerization;

[0118] S23, adding PEGDA, LiMATFSI and the second initiator to the solution obtained in step S22, stirring at 70° C. to obtain a uniform slurry;

[0119] S24, uniformly coating the slurry obtained in step S23 on a glass plate, irradiating with 365 nm ultraviolet light for 10 min to initiate free radical polymerization, and drying at 70° C. to obtain an initial single ion conductor interpenetrating network polymer electrolyte membrane containing POSS (hereinafter referred to as initial membrane);

[0120] S25, the initial film obtained in step S24 is placed on V EC / V DEC =1 / 1 electrolyte for 20 min to obtain a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS.

[0121] It should be noted that:

[0122] In step S21, the POSS material is a methacrylate type polyhedral oligomeric silsesquioxane (MAPOSS for short), such as one or more of heptaisobutyl methacryloyloxypropyl oligomeric silsesquioxane, heptaisooctyl methacryloyloxypropyl oligomeric silsesquioxane, heptaphenylvinyl oligomeric silsesquioxane, and heptaphenylallyl oligomeric silsesquioxane. In this embodiment, heptaisooctyl methacryloyloxypropyl oligomeric silsesquioxane is selected.

[0123] In step S21, the crosslinking agent is one or more of pentaerythritol tetraacrylate (PETEA), pentaerythritol triacrylate (PETA), trimethylolpropane triacrylate (TMPTA), and pentaerythritol tetra-3-mercaptopropionate. In this embodiment, PETEA is selected.

[0124] In steps S22 and S23, the initiator is one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP), benzoin diethyl ether, and benzoin dimethyl ether. In this embodiment, HMPP is used as the first initiator and the second initiator.

[0125] The amount of each substance used in each step is as follows:

[0126] PVDF-HFP: 10 parts, MAPOSS: 5 parts, PETEA: 1.5 parts, first HMPP: 0.5 parts, PEGDA: 35 parts, LiMATFSI: 30 parts, second HMPP: 0.7 parts.

[0127] In step S21, solvent A is one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, acetone, and isopropanol, and the amount used is 5 to 10 times the mass of PVDF-HFP. In this embodiment, solvent A is DMF, and the amount used is 6 times the mass of PVDF-HFP.

[0128] In step S21, solvent B is one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, acetone, and isopropanol, and the amount used is 5 to 10 times the mass of PVDF-HFP. In this embodiment, solvent B is isopropanol, and the amount used is 6 times the mass of PVDF-HFP.

[0129] Example 5

[0130] A method for preparing a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS, the steps are basically the same as those of the above-mentioned embodiment 4, except that:

[0131] In this embodiment, in step S21, the amount of MAPOSS is adjusted to 2.5 parts.

[0132] Example 6

[0133] A method for preparing a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS, the steps are basically the same as those of the above-mentioned embodiment 4, except that:

[0134] In this embodiment, in step S21, the amount of MAPOSS is adjusted to 10 parts.

[0135] Comparative Example 1

[0136] A method for preparing a single ion conductor interpenetrating network polymer electrolyte membrane without POSS, the steps are basically the same as those of the above-mentioned embodiment 4, except that:

[0137] In step S21, the precursor solution II does not contain POSS material, and only the cross-linking agent is added to the second solvent to dissolve to obtain the precursor solution II;

[0138] In the corresponding step S24, after slurry coating, free radical polymerization and drying, the initial membrane obtained does not contain POSS, and is used in the step S25 to be immersed in an electrolyte to obtain a single ion conductor interpenetrating network polymer electrolyte membrane that does not contain POSS.

[0139] Comparative Example 2

[0140] A method for preparing a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS by one-step photoinitiated polymerization, the steps are basically the same as those of the above-mentioned embodiment 4, except that:

[0141] In step S22, the first initiator is not added, and photo-initiated free radical polymerization is not performed.

[0142] In the corresponding step S24, after slurry coating, free radical polymerization and drying, the initial membrane obtained contains POSS, and is used in the step S25 to be immersed in an electrolyte to obtain a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS.

[0143] Comparative Example 3

[0144] A method for preparing a dual ion conductor interpenetrating network polymer electrolyte membrane containing POSS, the steps are basically the same as those of the above-mentioned embodiment 4, except that:

[0145] The LiMATFSI in S23 was replaced by an equimolar amount of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0146] In the corresponding step S24, after slurry coating, free radical polymerization and drying, the initial membrane obtained contains POSS, and is used in the step S25 to obtain a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS by soaking in an electrolyte. Application performance test:

[0147] The electrolyte membranes prepared in Examples 4 to 6 and Comparative Examples 1 to 3 were assembled into steel sheet|electrolyte|steel sheet CR2016 button cells, respectively, in the frequency range of 1.0×10 6 Hz~0.1Hz, AC impedance test is carried out at 25℃ and 75℃, according to the formula Calculate the ionic conductivity, where σ is the ionic conductivity; L is the thickness of the electrolyte membrane, which is 180 μm; S is the steel sheet electrode area, which is 2.06 cm 2 ; R is the resistance of the electrolyte membrane.

[0148] The AC impedance spectrum of the electrolyte membrane prepared in Example 4 is as follows: Figure 4 shown.

[0149] The electrolyte membranes prepared in Examples 4 to 6 and Comparative Examples 1 to 3 were assembled into lithium sheet|electrolyte|lithium sheet CR2032 button cells, respectively. The current and AC impedance of the cells before and after polarization were measured using the Bruce-Vincent-Evans method at room temperature. According to the formula Calculate the lithium ion migration number, where t Li + is the lithium ion migration number, ΔV is the polarization voltage, I0 is the initial current, I ss is the steady-state current, R0 is the initial impedance, R ss is the steady state impedance.

[0150] The electrolyte membranes prepared in Examples 4 to 6 and Comparative Examples 1 to 3 were assembled into lithium sheet|electrolyte|steel sheet CR2025 button batteries, respectively, and linear sweep voltammetry tests were performed at room temperature, with the starting voltage set to 0 V, the ending voltage set to 6 V, and the scan rate set to 0.01 V / s.

[0151] The electrolyte membranes prepared in Examples 4 to 6 and Comparative Examples 1 to 3 were respectively assembled into Li / LiFePO4 batteries, and the cycle performance test was carried out in a LAND CT2001A test system at 25° C., with a set voltage range of 2.5 to 4 V and a current density of 1C.

[0152] The test results of various embodiments and comparative examples are shown in Table 1.

[0153] Table 1 Ionic conductivity and lithium ion migration number of electrolyte membranes corresponding to Examples 4 to 6 and Comparative Examples 1 to 3

[0154]

[0155] Obviously, compared with the comparative example, the ionic conductivity and lithium ion migration number of Examples 4 to 6 are improved to a certain extent.

[0156] In summary, in embodiments 4 to 6 of the present invention, the single ion conductor polymer electrolyte has a higher lithium ion migration number than the traditional dual ion polymer electrolyte; the POSS structure is introduced into the single ion interpenetrating network polymer electrolyte, which can effectively promote ion transport, because the cage-like POSS molecules have a larger volume, which can disrupt the orderly arrangement of the polymer matrix and reduce its crystallinity. On the other hand, the POSS structure can further inhibit the movement of anions and obtain a higher lithium ion migration number.

[0157] Since the anions in single-ion conductor polymer electrolytes are fixed, they can largely eliminate polarization, even out lithium ion flux, and inhibit the formation of lithium dendrites. As an organic-inorganic hybrid material, POSS can directly participate in polymerization reactions and has better compatibility than traditional inorganic particles. The introduction of POSS structure into polymer electrolytes can not only improve the mechanical properties, electrochemical properties, thermal stability, etc. of polymer electrolytes, but also promote the formation of a stable electrode-electrolyte interface, which is beneficial to improving the cycle stability of the battery.

[0158] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A single ion conductor monomer, characterized in that: The single ion conductor monomer is a sulfonimide lithium salt monomer containing a methacrylamide structure, and the structural formula is:

2. The method for preparing a single ion conductor monomer according to claim 1, characterized in that: The intermediate II and lithium hydroxide are dissolved in a third solvent, methacryloyl chloride is added under low temperature, and then the product is extracted after sufficient reaction at 20 to 30° C. to obtain the single ion conductor monomer, wherein the low temperature environment is -5 to 5° C., the molar ratio of the intermediate II, methacryloyl chloride and lithium hydroxide is 1:(1 to 1.2):(1 to 1.2), and the structural formula of the intermediate II is:

3. The method for preparing a single ion conductor monomer according to claim 2, characterized in that: The preparation method of the intermediate II is as follows: dissolving the intermediate I, ferric chloride and palladium-carbon catalyst in a second solvent, adding hydrazine hydrate at 65-75° C., and continuing to reflux at 65-75° C. After the reaction is completed, extracting the product to obtain the intermediate II, wherein the mass ratio of the intermediate I, ferric chloride and palladium-carbon catalyst is 100:(3-10):(5-15); the mass ratio of the intermediate I and hydrazine hydrate is 1:(1.2-1.5), and the structural formula of the intermediate I is:

4. The method for preparing a single ion conductor monomer according to claim 3, characterized in that: The preparation method of the intermediate I is: dissolving trifluoromethanesulfonamide, p-nitrobenzenesulfonyl chloride and a strong base in a first solvent, and after sufficient reaction under a low temperature environment, extracting the product to obtain the intermediate I, wherein the molar ratio of trifluoromethanesulfonamide, p-nitrobenzenesulfonyl chloride and the strong base is 1:(1-1.2):(2-2.2).

5. Use of the single ion conductor monomer according to claim 1 in preparing a lithium ion battery electrolyte membrane.

6. A method for preparing a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS, characterized in that: The following steps are involved: S21, configure a precursor solution I containing poly (vinylidene fluoride - hexafluoropropylene), configure a precursor solution II containing a POSS material and a cross-linking agent; S22, after mixing the precursor solution I and the precursor solution II, adding the first portion of the initiator, stirring at 65-75° C. to form a uniform solution, and then irradiating with ultraviolet light for the first time to initiate free radical polymerization; S23, adding polyethylene glycol diacrylate, single ion conductor monomer and the second initiator to the solution treated in step S22, stirring at 65-75° C. to obtain a uniform slurry; S24, coating the slurry on a substrate to obtain a wet film, and subjecting the wet film to a second ultraviolet irradiation to initiate free radical polymerization, and then drying to obtain an initial film; S25, soaking the initial membrane in an electrolyte to obtain a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS; Wherein, the single ion conductor monomer structural formula is:

7. The method for preparing a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS according to claim 6, characterized in that: It also includes one or more of the following technical features: A, the POSS material is methacrylate type polyhedral oligomeric silsesquioxane; B. The crosslinking agent is one or more of pentaerythritol tetraacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate, and pentaerythritol tetra-3-mercaptopropionate; C. The first initiator is one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzoin diethyl ether, and benzoin dimethyl ether; D. The second initiator is one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzoin diethyl ether, and benzoin dimethyl ether; E. The mass ratio of poly(vinylidene fluoride-hexafluoropropylene), POSS material, crosslinking agent, the first initiator, polyethylene glycol diacrylate, single ion conductor monomer and the second initiator is: 10:(2.5-10):1.5:0.5:35:30:0.7; F. The solvent in the precursor solution I or the solvent in the precursor solution II is one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, acetone, and isopropanol.

8. The method for preparing a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS according to claim 6, characterized in that: The ultraviolet irradiation is performed at 365 nm ultraviolet light for 10 to 15 minutes.

9. The method for preparing a single ion conductor interpenetrating network polymer electrolyte membrane containing POSS according to claim 6, characterized in that: Step S25 also includes one or more of the following technical features: A. The electrolyte is in accordance with V EC / V DEC =1 / 1 electrolyte; B. The soaking time is 20 to 30 minutes.

10. A single ion conductor interpenetrating network polymer electrolyte membrane containing POSS, characterized in that: The single ion conductor interpenetrating network polymer electrolyte membrane containing POSS has a lithium ion transfer number of 0.78 to 0.85 and a lithium ion transfer number of 3.9 to 5.93×10 -5 S cm -1 Room temperature ionic conductivity.

Citation Information

Patent Citations

  • Preparation and application of single-ion conductive polymer electrolyte membrane

    CN110003399A

  • Single-ion polymer solid electrolyte with semi-interpenetrating network structure and preparation method of single-ion polymer solid electrolyte

    CN114865070A

  • Novel additive for non-aqueous electrolyte solution and lithium secondary battery comprising same

    CN117203817A

  • POSS-based zwitterionic polymer electrolyte membrane and preparation method thereof

    CN117865893A

  • Manufacturing method of planographic printing plate

    JP2020160348A